Problems Faced by Rural Women Entrepreneurs in Kandi Area of Punjab - Randhawa, Varinder; Gupta, Parul (Prabandhan: Indian Journal of Management, 2015)
Women entrepreneurs represent a group of women who have broken away from the beaten track and are exploring new avenues of economic participation. Among the reasons for women to turn to entrepreneurship include skill, knowledge, talents, abilities, and creativity in business and a compelling desire of wanting to do something positive. It is high time that countries should rise to the challenge and create more support systems for encouraging greater entrepreneurship amongst women. At the same time, it is up to women to break away from stereotyped mindsets. Keeping this in mind, the present study was undertaken with an objective to study the problems of the rural women entrepreneurs in Balachaur block of Nawanshahr District of Punjab. A sample of 28 women entrepreneurs was selected. The interview method was used to collect data from these women. Information on the entrepreneurial problems was gathered and analyzed. The results of the study revealed the major problems faced by women entrepreneurs (when they ventured out to carve their own niche in this tradition bound society called Kandi area of Punjab) were as follows : Personal (51%), socio-psychological (41%), technical (51%), financial (24%), production related (18%), and marketing (16%). Most of the problems faced by women were of personal, technical and socio-psychological nature. Thus, it was concluded that rural women possess the necessary characteristics and have the needed potential for running their homes and agro based micro enterprises successfully. However, the prerequisites to their entrepreneurial growth include education, skill based training, and infrastructural support together with the provision of credit facilities.